Creating a Learning Organisation : How to develop your leadership potential for professional success - Braham, Barbara J. (London : Kogan Page, 1995)
This work gives advice on educating staff in order to promote excellence. It indicates desirable practices, procedures and pitfalls, and shows managers how to encourage lifelong learning in their staff.
Keywords: Organizational effectiveness; Organizational change; Organizational learning